Case report: Tocilizumab for hypersensitivity reaction after oxaliplatin in a patient with NK/T-cell lymphoma - Juanyan Liao; Ming Jiang (Frontiers in Pharmacology)
Oxaliplatin-induced hypersensitivity reactions (HSRs) are commonly encountered in first-line therapies for various malignancies. Recent research indicates that these reactions can include cytokine release reactions (CRRs), which are characterized by a marked increase in interleukin-6 (IL-6) levels, sometimes rising as much as 40-fold. Standard management strategies for HSRs typically involve desensitization protocols and routine treatments. However, these conventional approaches may be insufficient for managing CRRs. Preliminary studies suggest that tocilizumab, an IL-6 receptor (IL-6R) antagonist, may play a crucial role in mitigating CRRs. In our case, a 65-year-old male with stage IV extranodal NK/T-cell lymphoma developed a severe HSR on day 1 following the infusion of oxaliplatin during his fourth chemotherapy cycle. This reaction was marked by a substantial increase in IL-6 levels. Despite the administration of standard treatments, including epinephrine and corticosteroids, the patient required ventilatory support and vasopressors on day 1. On day 2, tocilizumab was administered, resulting in a rapid and significant reduction in IL-6 levels. Subsequently, the patient’s symptoms, including fever, dyspnea, and hypotension, resolved, and he was discharged on day 5. This case demonstrates that tocilizumab can be an effective intervention in managing severe HSRs associated with CRRs. To our knowledge, this is the first reported instance of tocilizumab successfully salvaging a patient experiencing oxaliplatin-induced HSR. Nevertheless, further research is required to validate the efficacy of tocilizumab in treating oxaliplatin-induced HSRs.